1990
DOI: 10.1002/app.1990.070410938
|View full text |Cite
|
Sign up to set email alerts
|

A new method for rapid evaluation of long‐chain branching in polymers

Abstract: SynopsisA new method for rapid evaluation of long-chain branching (LCB) in polymers was developed. The crude GPC chromatogram and the measured value of intrinsic viscosity of the whole polymer are the only data required. By using trial and error in combination with graphic analysis, the threshold value Mo and average molecular weights M w and Mn, as well as LCB can be simultaneously evaluated. The advantage of this method lies in avoiding predetermination of the Mo for a given resin. The results obtained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…6,10,18,20 This secondary peak was not present in the response of the DRI and VD detectors, which is consistent with earlier on-line viscometer and SEC studies. [3][4][5][6][7]9,10 The difference in response between the LSD and the VD detectors is not surprising because it reflects the difference in sensitivity. The LSD signal is proportional to cM (c, concentration; M, molecular weight), while the VD response is proportional to cM ␣ where ␣ is the Mark-Houwink parameter.…”
Section: Resultsmentioning
confidence: 95%
“…6,10,18,20 This secondary peak was not present in the response of the DRI and VD detectors, which is consistent with earlier on-line viscometer and SEC studies. [3][4][5][6][7]9,10 The difference in response between the LSD and the VD detectors is not surprising because it reflects the difference in sensitivity. The LSD signal is proportional to cM (c, concentration; M, molecular weight), while the VD response is proportional to cM ␣ where ␣ is the Mark-Houwink parameter.…”
Section: Resultsmentioning
confidence: 95%
“…When considering the evaluation of the MWD by MHM approach, a remark should be made about the value of M 0 , i.e., the molecular weight value below which all the polymer chains are assumed to be linear. In the literature, approaches based on a double iteration over β and M 0 have been proposed . Accordingly, the value of M 0 is not an input parameter, but it is a result of the iteration procedure.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, approaches based on a double iteration over β and M 0 have been proposed. 22 Accordingly, the value of M 0 is not an input parameter, but it is a result of the iteration procedure. For the system under examination here, however, a sensitivity analysis has shown that the effect of M 0 on the MWD is substantially negligible.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have a steric hindrance and their reactivity with catalysts is very low. An alternative to avoid it is the oxidation andremoval of sulfur compounds [3][4] . oxidative desulfurization (ODS) is considered to be one of the promising new methods for super deep desulfurization of diesel oil.…”
Section: Introductionmentioning
confidence: 99%